A Modified Injector and Sample Acquisition Protocol Can Improve Data Quality and Reduce Inter‐Instrument Variability of the Helios Mass Cytometer. Issue 9 (30th July 2019) - Lee, Brian H.; Kelly, Geoffrey; Bradford, Shermineh; Davila, Melanie; Guo, Xinzheng V.; Amir, El‐Ad David; Thrash, Emily M.; Solga, Michael D.; Lannigan, Joanne; Sellers, Brian; Candia, Julian; Tsang, John; et al.
Abstract: Mass cytometry is a powerful tool for high‐dimensional single cell characterization. Since the introduction of the first commercial CyTOF mass cytometer by DVS Sciences in 2009, mass cytometry technology has matured and become more widely utilized, with sequential platform upgrades designed to address specific limitations and to expand the capabilities of the platform. Fluidigm's third‐generation Helios mass cytometer introduced a number of upgrades over the previous CyTOF2. One of these new features is a modified narrow bore sample injector that generates smaller ion clouds, which is expected to improve sensitivity and throughput. However, following rigorous testing, we find that the narrow‐bore sample injector may have unintended negative consequences on data quality and result in lower median and higher coefficients of variation in many antibody‐associated signal intensities. We describe an alternative Helios acquisition protocol using a wider bore injector, which largely mitigates these data quality issues. We directly compare these two protocols in a multisite study of 10 Helios instruments across 7 institutions and show that the modified protocol improves data quality and reduces interinstrument variability. These findings highlight and address an important source of technical variability in mass cytometry experiments that is of particular relevance in the setting of multicenter studies. © 2019 International Society for Advancement of Cytometry Abstract :